Assessment of the level of knowledge of prescription of nsaids for horses in northeastern brazil (Research, Society and Development, 2022)
In the present study, 100 questionnaires were applied (50 per group) with the objective of identifying which are the main NSAIDs recommended by veterinarians (G1) and agricultural store salespeople (G2) in the Northeast region of Brazil for the treatment of disorders of the systems. Locomotor and digestive system of the equine species. For disorders of the locomotor system: as a first option, phenylbutazone was described as the main NSAID in both groups (G1: 58% and G2: 28%). As a second option, flunixin meglumine was the most recommended (G1: 32% and G2: 24%). As a third option, meloxicam was also the most recommended by both (G1: 26% and G2: 16%). For disorders of the digestive system: as a first option, flunixin meglumine was the most recommended drug (G1: 54% and G2: 40%). As a second option, for G1, flunixin meglumine (36%) and for G2, dipyrone (30%). As a third option, for G1, meloxicam and DMSO were the most cited (18% each) and for G2, phenylbutazone (18%). Non-selective NSAIDs are the most recommended by veterinarians and sellers of agricultural stores in Northeast Brazil for the treatment of locomotor and digestive disorders in horses, while selective COX-2 inhibitors are still poorly recommended. Ignorance of technical dosages was observed in both groups, with emphasis on G2. Control measures in the sale of NSAIDs and guidance on their correct use to horse professionals are necessary.